Budgetary control of Australian police services and the new governance of security - Dupont, Benoit (2005)
Through the example of the Australian police services, this article examines the impact of the New Public Management tools on strengthening administrative accountability. Governments, faced with increasing social demand for security, have launched into political auctions on the themes of police activity and social control. Relationships between the authorities and the police administrators have been redefined, mainly through more rigorous budgetary control. After a rapid examination of the administrative context that led to the implementation of programme budgeting - the main government tool in this area - the article examines the tensions that resulted from its introduction. Particular emphasis is placed upon the limitations of such a tool in the field of security, which is undergoing profound reconfiguration as a result of increasingly frequent cooperation betwene public, private and hybrid actors. - Reproduced.
Keywords: Police - Australia; Police